The Effectiveness of Animated Videos in Health Education: Improving Knowledge, Attitudes, and Behaviors - Haris, Abdul; Swarjana, I Ketut; Darmini, Anak Agung Ayu Yuliati; Rahyanti, Ni Made Sri (Universitas Padjadjaran, 2026)
Background: Health education plays a crucial role in enhancing the knowledge, attitudes, and behaviors of the community. Animated videos have become an increasingly popular educational method due to their ability to present complex information in an engaging manner. However, systematic mapping of their effectiveness is still lacking. Objective: This scoping review aims to clarify the evidence of the effectiveness of animated video-based health education in improving knowledge, attitudes, and behaviors. Methods: This literature review employs the PCC model (P: Patients, Families, Community; C: Health Education Attitudes and Behaviors; C: Animated Videos, Digital Media) to identify relevant literature. Inclusion criteria consisted of articles published in English within the last 10 years, while narrative articles, integrative reviews, scoping reviews, systematic reviews, and meta-analyses were excluded. The results of the analysis are reported in accordance with the PRISMA-ScR guidelines. Results: Out of 578 identified articles, 12 met the inclusion criteria. Conclusion: Animated educational videos have proven effective in enhancing knowledge and attitudes. The implications for nursing practice include the development of video-based educational materials to improve communication and understanding among patients regarding complex health issues.